2018
DOI: 10.1016/j.atherosclerosis.2018.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Apoliporotein L3 interferes with endothelial tube formation via regulation of ERK1/2, FAK and Akt signaling pathway

Abstract: Members of the Apolipoprotein L family (APOL) are induced in endothelial cells by a variety of inflammatory stimuli. • APOL3 is the only APOL commonly induced by atherogenic stimuli such as thrombin, MPO or oxidized LDL. • APOL3 is also induced by angiogenic stimuli such as VEGF and FGF. • APOL3 invalidation decreases tubulogenesis and endothelial wound repair. It increases endothelial permeability. • APOL3 invalidation correlates with inhibition of pro-angiogenic pathways and reduces expression of pro-angioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Endothelial function decreases during PE, and endothelial dysfunction is a characteristic of atherosclerosis. ApoL3, as a regulator of MAPK and FAK signaling in endothelial cells, has been shown to be involved in angiogenesis in vitro (Khalil et al, 2018). Increased ApoL3 in PE may be a compensatory response to endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function decreases during PE, and endothelial dysfunction is a characteristic of atherosclerosis. ApoL3, as a regulator of MAPK and FAK signaling in endothelial cells, has been shown to be involved in angiogenesis in vitro (Khalil et al, 2018). Increased ApoL3 in PE may be a compensatory response to endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Pintus et al reported that activation of the PKC/Raf/MEK/ERK pathway could regulate blood lipid levels and increase the risk of atherosclerosis by increasing the expression of native LDL and E2F-1. 32 The activation of ERK1/2 plays an important role in this pathway 33,34 and inhibition of ERK1/2 activation can inhibit the phosphorylation of MAPK, thereby regulating cell proliferation and migration. In addition, the activation of ERK1/2 can increase the expression of the downstream nuclear transcription factor NF-κB and the cell cycle proteins, such as Cyclin D1, which leads to a change in cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gaudet et al [31] reported that IFN-γinduced APOL3 was a potent bactericidal agent protecting multiple non-immune barrier cell types against infection. Besides, the phenotype of APOL3 KO podocytes exhibits striking similarities to that resulting from cancer metastasis, with strong reduction of cellular adherence and increase in cell motility [27]. In cancer, the APOL3-controlled NCS-1 is known to promote motility, metastatic spread and survival of cancer cells [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…As an apolipoprotein, APOL3 was reported in many cell types, such as endothelial cells [27], podocyte [28], neurones [29], trypanosomes [30]. Recently, Gaudet et al [31] reported that IFN-γinduced APOL3 was a potent bactericidal agent protecting multiple non-immune barrier cell types against infection.…”
Section: Discussionmentioning
confidence: 99%